PARTISIPASI KELOMPOK TANI DALAM PENINGKATAN PRODUKTIVITAS TANAMAN PADI DI KAWASAN PERTANIAN KECAMATAN KOTO TANGAH TAHUN 2020. - Annisa Aulia Ali; Ratna Wilis (JURNAL BUANA, 2022)
Annisa Aulia Ali. FARMER GROUP PARTICIPATION IN INCREASING RICE PRODUCTIVITY IN AGRICULTURAL AREA, KOTO TANGAH DISTRICT IN 2020. Thesis, Padang: Faculty of Social Sciences. Padang State University. 2021 The aims of this study were (1) to determine the level of participation of farmer groups in the agricultural area of Koto Tangah District in 2020. (2) To calculate the productivity of rice plants in the agricultural area of Koto Tangah District in 2020. The research method used was a mixed method as the basic method. , namely quantitative descriptive supported by qualitative methods used both simultaneously or simultaneously. Data collection techniques in this study are questionnaires, interviews and documentation. The data analysis technique is to use Sequential Exploratory Design, namely qualitative research is carried out first and then the results are analyzed, then continued with or used to build the second (quantitative) stage. The results of this study are (1) The level of participation of rice farmer groups in Koto Tangah District in 2020 as a whole is at a score with an interpretation based on intervals, which is sufficient, which is 61.2%. Some of the participations such as participation in meeting, planting paddy fields, harvesting and post-harvesting, extension activities, monitoring group activities, and measuring farming results received scores with high interpretations. And participation in decision-making activities as well as participation in contribution activities must get a score with sufficient interpretation. This illustrates that although 2020 was the year the COVID-19 pandemic entered Indonesia, the level of participation of farmer groups in increasing rice crop productivity was in good condition and running well. (2) There is a productivity level above the average yield of rice productivity according to the Padang City Agriculture Service in the Padang City Central Statistics Agency in 2020 for Koto Tangah District, which is >5.6 Tons/Year. The level of rice productivity in farmer groups in Koto Tangah District based on the results of research in the field, the highest was found in 4 groups of rice farmers, namely the Budi Sepakat, Berkah, Sikayan and Limpur Sepakat rice farmer groups which reached 12 tons/year. Meanwhile, the lowest rice productivity in farmer groups is found in Sawah Laweh and Banda Langik farmer groups which only reach 4 tons/year. Keywords: Participation, Agriculture, Productivity